2021
DOI: 10.1007/s12564-021-09694-w
|View full text |Cite
|
Sign up to set email alerts
|

Post-pandemic reflections: lessons from Chinese mathematics teachers about online mathematics instruction

Abstract: This study investigated how teachers in China perceived the effects of online instruction on mathematics learning and examined the challenges they encountered when the country shifted to online instruction during the COVID-19 pandemic. We interviewed 152 mathematics teachers from 20 cities (municipalities) or provinces in China and adopted the four-component didactic tetrahedron model (teacher, technology, student, and mathematics) to identify their struggles with technology, teacher–student interactions, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 24 publications
1
37
0
7
Order By: Relevance
“…In the context of university education, teachers are expected to evolve rapidly in the technological world, as higher education institutions play a crucial role in developing the digital competence of tomorrow's professionally active citizens [6]. However, the effectiveness of this development can only be assessed by evaluating the teachers' perception of the use of DCC tools and the teaching results obtained in the classroom on concrete actions [7][8][9]. In this area, it has been found that the positive perception of the use of DCC tools in the classroom by teachers does not always coincide with the real capacity of teachers to adapt their programs to the virtual classroom with digital resources [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…In the context of university education, teachers are expected to evolve rapidly in the technological world, as higher education institutions play a crucial role in developing the digital competence of tomorrow's professionally active citizens [6]. However, the effectiveness of this development can only be assessed by evaluating the teachers' perception of the use of DCC tools and the teaching results obtained in the classroom on concrete actions [7][8][9]. In this area, it has been found that the positive perception of the use of DCC tools in the classroom by teachers does not always coincide with the real capacity of teachers to adapt their programs to the virtual classroom with digital resources [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…A meta-pedadidactic is the educator's ability to comprehensively analyze pedagogy interaction, didactic interaction, and didactic pedagogy anticipation in a learning situation (Suryadi, 2013). The rapid development of technology expands to the issue of technology integration into didactic mathematics systems (Ruthven, 2012;Cao, et al, 2021). The situation in online learning is undoubtedly different from the situation in face-to-face learning because of the difference in the milieu.…”
Section: Didactical System In Online Learning Environmentmentioning
confidence: 99%
“…Before the COVID-19 pandemic, WBMI was widely used in distance education at the undergraduate level (Cao et al, 2021 ). There have only been a few research that examined the nature of the web-based mathematics learning environment (Cady & Rearden, 2009 ; Cao et al, 2021 ).…”
Section: Potential Moderators Of the Effectiveness Of Wbmi On Mathema...mentioning
confidence: 99%
“…Web-based mathematics instruction (WBMI) plays a crucial role in mathematics education as technological advancements have changed the way of learning and teaching mathematics (Cao et al, 2021 ). Although WBMI has been initially seen only as a preferred teaching option in graduate and undergraduate education, it has been widely used at all levels of K-16 education in recent years.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation